EFEKTIFITAS SANKSI PIDANA DALAM IMPLEMENTASI UNDANG-UNDANG NOMOR 30 TAHUN 2000 TENTANG RAHASIA DAGANG - , PRAMANA SYAMSUL IKBAR; , Dr. Sulistiyowati S.H., M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The protection of confidential information or widely known as commercial in confidence in Indonesia is regulated in Law number 30 of 2000 on Commercial in Confidence. The law is too short and too general compared to other laws concerning intellectual property rights (IPR). Consequently, it becomes highly potential of causing various interpretations and confusions among business players. In fact, the protection on commercial in confidence is getting more important lately as the information-based business trend developed. The undisclosed information becomes the companyâs important asset they have to keep from the competitors. However, problems arise as the legal sanctions extracted from the law have not been effectively implemented. It then results in confusion on what the concrete forms of protecting confidential information are, what to do to avoid unfair competition, and so on. Management of commercial in confidence becomes a very crucial need of companies, industries, or other businesses, because they could get significant advantages and benefits from it. This study is conducted by the normative-empirical approach and is supported by relevant data. The result shows that â analyzed from the legal economic aspects â protection of commercial in confidence is a business asset that could be used to avoid unfair competition. Meanwhile, the socialization of commercial in confidence must continuously be carried out, in terms of both quality and quantity. Thus, a government regulation on the lawâs implementation or the revision of Law number 30 of 2000. Therefore, in order to get verifiable description of the answers, a descriptive analysis of normative-empirical research on that matter is conducted, by references of the legal norms applied in Indonesia compared to the courtsâ decisions as the secondary data and primary data sources of the peace officers. In conclusion, the process of settling disputes of commercial in confidence is not yet an effective solution of ultimum remedium to the violations or criminal acts of commercial in confidence.